2021
DOI: 10.1186/s12890-021-01688-z
|View full text |Cite
|
Sign up to set email alerts
|

Underdiagnosis of obstructive lung disease: findings from the French CONSTANCES cohort

Abstract: Background The burden of undiagnosed obstructive lung disease (OLD) (mainly asthma and chronic obstructive pulmonary disease) is not fully established, and targets for corrective action are yet to be identified. We assessed the underdiagnosis of OLD and its determinants in France. Methods CONSTANCES is a French population-based cohort of adults aged 18–69 years at inception. We analysed data collected at inclusion in 2013–2014. Undiagnosed OLD was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, when patients present with respiratory symptoms suggestive of airways disease, it is important to consider the possibility of asthma or COPD (referred to as case finding), as these conditions are also often missed. 16 Typical asthma symptoms include wheeze, shortness of breath, and chest tightness. Specific clues include worsening of these symptoms at night or early in the morning, the variable and episodic nature of symptoms, and triggers for symptoms (eg, viral infections, exercise, allergens, and irritants such as strong smells or cold air).…”
Section: Approachmentioning
confidence: 99%
“…However, when patients present with respiratory symptoms suggestive of airways disease, it is important to consider the possibility of asthma or COPD (referred to as case finding), as these conditions are also often missed. 16 Typical asthma symptoms include wheeze, shortness of breath, and chest tightness. Specific clues include worsening of these symptoms at night or early in the morning, the variable and episodic nature of symptoms, and triggers for symptoms (eg, viral infections, exercise, allergens, and irritants such as strong smells or cold air).…”
Section: Approachmentioning
confidence: 99%
“…Indeed, in an international study in 70 countries, one-third of French participants aged 18–45 years with asthma symptoms (attacks of wheezing or whistling breath in the past 12 months) were not diagnosed with asthma 25. In addition, in a recent paper by Delmas et al 26, with data from the CONSTANCES cohort, 64.4% of participants with airflow limitation did not report a previous diagnosis of obstructive lung disease (asthma, COPD or bronchiectasis). This score has the advantage of characterising and quantifying asthma symptoms in participants who have never been labelled as asthmatics.…”
Section: Discussionmentioning
confidence: 96%
“…Third, the potential bias of self-reporting asthma may have led to misclassification of asthma that should be another obstructive respiratory disease, such as COPD [33]. Numerous studies have indicated that asthma-COPD phenotype overlap syndrome frequently leads to undiagnosed asthma [34,35].…”
Section: Plos Onementioning
confidence: 99%